Religious life or consacrated life? - González Faus, José Ignacio (Razón y fe, 2019)
The current crisis of religious life is not only quantitative but also qualitative: the religious life of the future must be like the spearhead of a change that all Christianity needs and that J. B. Metz described years ago as going beyond bourgeois religion. In a world that is like a globalization of Nazi Germany (where citizens who live well coexist with extermination camps, cremation shelters, genocides and so on, without the former wanting to know anything about the latter), the Church must be a “confessing” church, with the terminology used by D. Bonhoeffer in Hitler’s time and as the church was born before the Roman Empire: a confession directed then against the divinity of the emperor and today against the divinity of money. Religious life should be the vanguard of this confessional community, going from the status perfectionis (always threatened to degenerate into pharisaism) to the status confessionis. The three classical vows then receive a more authentically evangelical sense, which places them beyond the bourgeois religion.
Keywords: bourgeois religion; concentration camps; consecrated life; confessing community